STUDI EKSPERIMENTAL WIND TUNNEL TIPE SUBSONIC RANGKAIAN TERBUKA DENGAN VARIASI BENTUK HONYECOMB - Azis, Andy; Alchalil, Alchalil; Setiawan, Adi; Islami, Nurul (E-Journal Universitas Malikussaleh, 2023)
Honeycomb is applied to the Open Series Subsonic Wind Tunnel which aims to obtain a unidirectional fluid flow shape with uniform (laminar) and stable fluid flow velocities. Honeycomb testing was carried out experimentally at a flow velocity of 3 m / s without honeycomb using a variety of shapes: hexagonal, square, and circular. Each honeycomb shaped to 8mm diameter. The results of the analysis on honeycomb testing with variations in shape obtained the value of turbulence intensity that occurs in the test section, namely for hexagonal shape variations the flow that occurs is better than circular shape, while in circular shape variations the value of turbulence intensity is better than square shape. The results of the Reynold's number calculation show that the flow that occurs is laminar with the following values, in the hexagonal shape variation the value is 787, circular shape 956.48, and square shape 1199.42. After calculating the turbulence intensity and Reynold's number, we can conclude that honeycomb with hexagonal shape variation is optimal than circular shape, and circular is optimal than square.